Influence of dimethoxymethane addition on performance, emission and combustion characteristics of the diesel engine. Issue 6 (18th August 2017) - Deepanraj, B.; Sankaranarayanan, G.; Senthilkumar, N.; Pugazhvadivu, M.
Abstract: This paper assesses the effects of dimethoxymethane (DMM) blends on combustion characteristics, fuel economy, emissions and engine's power. Experiments were carried out on a single-cylinder, four-stroke compression ignition engine of direct injection with volume fractions of DMM blends of 5%, 10%, 15% and 20% v/v starting from base diesel. Experimental results suggest that 20% DMM blended with diesel achieved better performance in terms of efficiency as well as in exhaust emissions. Carbon monoxide emission levels, hydrocarbon and smoke are reduced considerably with DMM additions, while the oxides of nitrogen emission in exhaust increase due to higher in-cylinder temperature. The oxygen content in the DMM blends plays a greater role in the combustion process compared to neat diesel fuel. The combustion profile was smoother, and no knocking was experienced while operating with DMM blends. Also, it is observed that addition of DMM in diesel shortens the ignition delay and total combustion duration.